2017
DOI: 10.1016/s2095-3119(16)61460-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of parameters affecting Agrobacterium-mediated transient expression in citrus

Abstract: Agrobacterium-mediated transient expression assays are a convenient alternative to stable expression because they are simple, easy to perform, and achieve gene expression rapidly. This study investigated the factors affecting transient gene expression efficiency in citrus by observing the cryo-sectioning of leaf samples under a laser confocal microscope. These factors included the composition of the infiltration buffer, the Agrobacterium cell density, the leaf development stage, the incubation temperature, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Furthermore, a slightly acidic pH of MES buffer (5.6) is probably more favorable for the expression of vir genes, as shown by Manfroi et al [53]. Li et al also showed that different infiltration buffers and their concentrations can significantly affect the Agrobacterium-mediated transformation efficacy of citrus plants [54]. The highest expression level was obtained using a buffer containing 15 mM of MES + 10 mM MgCl 2 + 200 μM acetosyringone.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, a slightly acidic pH of MES buffer (5.6) is probably more favorable for the expression of vir genes, as shown by Manfroi et al [53]. Li et al also showed that different infiltration buffers and their concentrations can significantly affect the Agrobacterium-mediated transformation efficacy of citrus plants [54]. The highest expression level was obtained using a buffer containing 15 mM of MES + 10 mM MgCl 2 + 200 μM acetosyringone.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, we used the 35S promoter of CaMV, which is reported as a strong constitutive promoter and has been used extensively to drive the expression of several proteins in plants [66,67]. However, the expression levels under the control of this promoter vary greatly depending on the different factors such as the design of expression cassette, plant host, transformation efficiency and growth conditions [54,68]. Further improvement of the IHNV-G protein expression could be achieved by optimizing these factors.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the mutated Cas-base editors produce single mutations in the target DNA specifically and precisely (base editing). Base editing has been adopted in plant species (Figure 2), such as watermelon (Li et al, 2017;Lu and Zhu, 2017;Ren et al, 2018;Tian et al, 2018), to produce transgene-free homozygous als (acetolactate synthase) mutant plants, resistant to the herbicide tribenuron (Tian et al, 2018). In addition to base editing, other applications of CRISPR/dCas9 in plants have been recently reviewed, including gene induction and suppression, epigenetic variations, and DNA-free modifications (Moradpour and Abdulah, 2020).…”
Section: Techniques and Methodologies For Genome Editingmentioning
confidence: 99%
“…Transient gene expression assays, performed via Agrobacterium infiltration in grapefruit leaves, have demonstrated that transient transformation efficiency can be influenced by different factors, such as infiltration medium, Agrobacterium concentration, and leaf development stage (Figueiredo et al, 2011). Li et al (2017) showed that sweet orange leaves approaching full maturity were at an optimal, in terms of transient protein expression using Xcc-facilitated agroinfiltration (Jia and Wang, 2014).…”
Section: Transformation and Regeneration: The Main Bottlenecks Of Newmentioning
confidence: 99%
“…Agroinfiltration procedure was implemented in Mexican lime using intermediate-aged leaves and setting Agrobacterium concentrations and buffer composition [71]. In addition, a pre-treatment with Xanthomonas citri (Xcc) before Agrobacterium infection significantly enhanced transient protein expression in different citrus species (Duncan grapefruit, Valencia orange, Key lime, Carrizo citrange, sour orange, and Meiwa kumquat), eliciting cell divisions [72,73].…”
Section: Citrus Transformation Protocolsmentioning
confidence: 99%